2016
DOI: 10.18632/oncotarget.12944
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting glutaminase in acute myeloid leukemia: metabolic dependency of selected AML subtypes

Abstract: Metabolic reprogramming has been described as a hallmark of transformed cancer cells. In this study, we examined the role of the glutamine (Gln) utilization pathway in acute myeloid leukemia (AML) cell lines and primary AML samples. Our results indicate that a subset of AML cell lines is sensitive to Gln deprivation. Glutaminase (GLS) is a mitochondrial enzyme that catalyzes the conversion of Gln to glutamate. One of the two GLS isoenzymes, GLS1 is highly expressed in cancer and encodes two different isoforms:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 41 publications
6
150
1
Order By: Relevance
“…Although the glutamine dependence of some NSCLC cells is lost when they are grown in vivo , the canonical anaplerotic role of glutamine prevails in other contexts in vivo [9, 10, 12, 1416, 30], and clinical trials of the GLS inhibitor CB-839 have yielded some promising results [8] suggesting that these recent observations in NSCLC models is certainly not general to all cancers. It is also important to note that the dispensability of glutamine in certain circumstances does not imply that anaplerosis in these cells is not required; as discussed above, cancer cells can find alternative ways to maintain an anaplerotic flux.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the glutamine dependence of some NSCLC cells is lost when they are grown in vivo , the canonical anaplerotic role of glutamine prevails in other contexts in vivo [9, 10, 12, 1416, 30], and clinical trials of the GLS inhibitor CB-839 have yielded some promising results [8] suggesting that these recent observations in NSCLC models is certainly not general to all cancers. It is also important to note that the dispensability of glutamine in certain circumstances does not imply that anaplerosis in these cells is not required; as discussed above, cancer cells can find alternative ways to maintain an anaplerotic flux.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many tumors rely on glutamine-mediated TCA cycle anaplerosis in vivo with concordance of glutamine dependence ex vivo and in vivo . (see Table 1), as discussed in detail below [9, 10, 12, 14, 15, 30] (Figure 2). Thus, recent observations in certain NSCLC mouse tumors cannot be generalized to other cancers.…”
Section: Culture Conditions and Model Systems Influence Glutamine Metmentioning
confidence: 99%
“…Several recent studies have shown that targeting glutamine uptake or metabolism can have anti-leukemic activity in AML 13,15,16,27,28 . However, most of these studies have focused on the role of glutamine in supporting energy metabolism rather on its role in maintaining redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The human gastrointestinal tract is a main site of glutamate utilization with more than half of the glutamine obtained from systemic circulation utilized here. Glutamine has various effects on the structure and function of the tract and any change in glutamine metabolism may further cause the damage in gastrointestinal tract [45][46][47].…”
Section: Discussionmentioning
confidence: 99%